2013
DOI: 10.1007/s00198-013-2456-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the dynamic radiographs for diagnosing acute osteoporotic vertebral fractures

Abstract: Dynamic radiographs provide a convenient way to identify acute OVFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The present conservative treatment protocol was as follows: all patients with the suspicion or the diagnosis of OVF were admitted. The fractures were confirmed by MRI, computed tomography (CT) scan, and dynamic X-ray in standing and supine position [ 19 ]. From these imaging examinations, patients with definitive diagnosis of OVF were forbidden to sit up even for dietary intake and evacuation during the initial 2 weeks [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present conservative treatment protocol was as follows: all patients with the suspicion or the diagnosis of OVF were admitted. The fractures were confirmed by MRI, computed tomography (CT) scan, and dynamic X-ray in standing and supine position [ 19 ]. From these imaging examinations, patients with definitive diagnosis of OVF were forbidden to sit up even for dietary intake and evacuation during the initial 2 weeks [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plain dynamic loading radiography improves the diagnostic accuracy of OVFs at the time of the initial visit [5]. In addition, this study demonstrated that plain dynamic loading radiography is an extremely useful imaging tool for the quantitative evaluation of vertebral body instability.…”
Section: Discussionmentioning
confidence: 66%
“…Second, the cases included were limited to fractures affecting the thoracolumbar junction, and patients with secondary osteoporosis were excluded; therefore, the findings of the present study cannot be generalized to all kinds of OVFs. However, in clinical settings, particularly in postmenopausal women, secondary osteoporosis accounts for approximately 20% or <30% of all cases of osteoporosis [24,25], and fractures of the thoracolumbar junction account for the majority of OVFs [5,6]. Although a larger study is needed to confirm and generalize the results of the present study for all OVF cases, a plain dynamic loading radiography is an extremely useful imaging tool, which allows for the resistance of OVFs to conservative treatment to be quantitatively evaluated based on vertebral body instability in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations